PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN AUDIO VISUAL TERHADAP PEMAHAMAN KONSEP SISWA KELAS X SMA N 6 SEMARANG TAHUN PELAJARAN 2014/2015 - Hartuti Hartuti; Ernawati Saptaningrum; Ngurah Ayu Nyoman Murniati (Jurnal Penelitian Pembelajaran Fisika, 2015)
Lack of understanding of the concept of students due to the learning activities that are less attractive so that students are less active in responding to material that has been presented by the teacher. Students are less able to solve the existing problems in the questions so that students feel bored and tired that resulted in the concept of understanding is low. It takes a model of learning and appropriate learning media that can enhance students' understanding of concepts so that students interested in learning and play an active role in learning.This study aims to determine the effect of problem based learning model of audio-visual assisted towards understanding the concept student of class X SMA N 6 Semarang school year 2014/2015. The study design used is pretest-posttest control group design. The population was all students of class X MIA SMA N 6 Semarang. Sampling using cluster random sampling. The study sample was taken two pieces of class, a class X MIA 4 as class experiments using problem-based learning models assistance audio-visual and class X MIA 6 as the control class using a model of problem based learning without audio-visual assisted.Analysis of the early stages of using the value of midterms showed that both classes normally distributed and homogeneous. Based on the results of the  test analysis right on the experimental class and control class that is  = 2.15>  = 1.67 so that  is rejected. While the gain obtained from test analysis < > experimental class by 0.613 and < > 0.596 the control class is the second class to increase understanding of the concept of the category of being. From the above results it can be concluded that the model of problem-based learning-assisted audio visual effect on student’s understanding the concept of class X SMAN 6 Semarang school year 2014/2015.